Being pro-active in meeting the needs of suicide-bereaved survivors: results from a systematic audit in Montréal - Fabienne Ligier; Jessica Rassy; Gabrielle Fortin; Ian van Haaster; Claude Doyon; Charlie Brouillard; Monique Séguin; Alain Lesage (BMC, 2020)
Abstract Background Suicide is a major public health concern. In 2017, the suicide rate in Canada was 11 per 100,000 inhabitants. According to literature, 1 in 5 people have experienced a death by suicide during their lifetime. The aim of this study was to describe the met and unmet needs of suicide-bereaved survivors and to provide postvention recommendations. Methods Further to an exploratory mixed-method audit of 39 suicides that occurred in Montreal (Canada) in 2016, suicide-bereaved survivors (n = 29) participated in semi-structured interviews and completed instruments to discuss and assess potential pathological grief, depression (PHQ-9), and anxiety (GAD-7), as well as health and social services utilization. A panel then reviewed each case and provided recommendations. The mean age of participants was 57.7 years and 23 were women. Results Although help was offered initially, in most cases by a health professional or service provider (16/29), 22 survivors would have liked to be contacted by telephone in the first 2 months post suicide. Four categories of individual unmet needs (medical/pharmacological, information, support, and outreach) and one collective unmet need (suicide pre/postvention training and delivery) emerged. Conclusions Although Quebec provincial services have been developed and offered to suicide-bereaved survivors in the past decade, many dwindled over time and none has been applied systematically. Recommendations for different stakeholders (Ministry of Health and Social Services, coroners, NGOs, and representatives of suicide-bereaved survivors) outlined in this study could be an interesting first step to help develop a suicide pre/postvention strategy.